1975
DOI: 10.1002/eji.1830050816
|View full text |Cite
|
Sign up to set email alerts
|

Participation of immunoglobulin‐bearing lymphocytes in the production of macrophage migration inhibitory factor

Abstract: The role of immunoglobulin-bearing cells in the production of macrophage migration inhibitory factor (MIF) by tuberculin-stimulated lymphocytes of guinea pigs, immunized with complete Freund's adjuvant, was studied. It was found that: (1) pretreatment of lymphocytes with rabbit anti-guinea pig IgG (anti-IgG) does not block antigen-induced MIF production. (2) Passage of lymphocytes through double layer IgG-anti-IgG gelatin bead columns (the preparation of which is described) abolishes MIF formation by the elute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1976
1976
1979
1979

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Anti-Ig was also reported of being incapable to induce lymphocyte pro liferation, unless the cells originated from aged mice [41]. We have reported [28] suc cessful induction of MIF production by an ti-IgG in the guinea pig but similar experi ments performed in the rabbit were negative [24].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Anti-Ig was also reported of being incapable to induce lymphocyte pro liferation, unless the cells originated from aged mice [41]. We have reported [28] suc cessful induction of MIF production by an ti-IgG in the guinea pig but similar experi ments performed in the rabbit were negative [24].…”
Section: Discussionmentioning
confidence: 82%
“…In humans, it was found that both B and T cells are capa ble of PPD-induced MIF production, B cells being more efficient [18,32]. In the guinea pig, it was shown by Bloom et al [5] and by us [28] that most if not all MIF pro ducers in PPD-stimulated cultures are B cells.…”
Section: Discussionmentioning
confidence: 90%
“…Until recently, this reaction was generally considered as one of the parameters of CMI, because by indirect arguments (for references see reference 12) it was assumed, and by direct cxperiments (4,5,8) it was demonstrated that T cells, the carrier of CMI, are the source which produces a mediator (MI-factor) responsible for the inhibition of macrophage migration. Now, reports accumulate which show that besides T cells also B cells can produce MI-factor (12,14,27,29) and therefore it is made dubious if the MI-test is convenient to demonstrate CMI.…”
Section: Discussionmentioning
confidence: 99%